A Pilot Randomized Controlled Clinical Trial to Assess Tolerance and Efficacy of Navy Bean and Rice Bran Supplementation for Lowering Cholesterol in Children. (16th February 2017) - Borresen, Erica C.; Jenkins-Puccetti, NaNet; Schmitz, Katie; Brown, Dustin G.; Pollack, Austin; Fairbanks, Amanda; Wdowik, Melissa; Rao, Sangeeta; Nelson, Tracy L.; Luckasen, Gary; Ryan, Elizabeth P.
Background: Navy beans and rice bran demonstrate efficacy to regulate serum cholesterol in hypercholesterolemic adults; however, the cardiovascular disease (CVD) protective properties of these foods in children are unknown and merit investigation.Objective: The objectives were to determine whether cooked navy bean powder (NBP) and/or heat-stabilized rice bran (RB) supplementation is tolerable, improves dietary fiber intake in children, and modulates lipid profiles.Methods: Children aged 8 to 13 years at risk for CVD due to abnormal lipids were recruited. Elevated cholesterol levels were defined as total cholesterol ≥180 mg/dL and high-density lipoprotein (HDL) <60 mg/dL; low-density lipoprotein (LDL) ≥100 mg/dL and HDL <60 mg/dL; or non-HDL >100 mg/dL and HDL <60 mg/dL. Participants completed a pilot 4-week, randomized controlled, 4-arm dietary intervention. They consumed study-provided muffins or a smoothie daily that included 0 g NBP or RB (control), 17.5 g NBP, 15 g RB, or a combination 9 g NBP + 8 g RB. Fasting blood was collected at baseline and week 4. Participants also completed 3-day food logs and gastrointestinal health questionnaires. Results: Thirty-eight children completed the trial (n = 9 control, n = 10 NBP, n = 9 RB, and n = 10 NBP + RB groups). Only 3 participants withdrew due to noncompliance of required food consumption. Participants in the intervention groups significantly increased intake of NBP and RB at week 4 (p≤.01). The NBP and NBP + RB groups increased total fiber intake from baseline to week 4 (p=.02 and p=<.01, respectively). HDL-cholesterol was higher in NBP-group participants compared to control at week 4 ( P = .02).Conclusion: Increasing NBP and/or RB intake is tolerable for children, and our findings suggest higher daily intakes are needed for a longer duration to induce favorable changes across multiple serum lipid parameters.